A Review of Systematic Methodologies for Shipyard Facility Layout Design - Pambudi, Ghulam Tulus; Gunawan, Gunawan; Muzhoffar, Dimas Angga Fakhri; Sari, Wanda Rulita (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
The dynamic and complex nature of the shipbuilding industry necessitates efficient facility layout planning to optimize operational efficiency and minimize costs. Traditional layout design approaches, often based on practical experience, fall short of achieving optimal results. This paper reviews three advanced methodologies for shipyard facility layout design: heuristic algorithms, Systematic Layout Planning (SLP), and graph theory. Heuristic algorithms, including genetic algorithms and simulated annealing, offer flexible and rapid solutions but may not always achieve global optimization. SLP provides a structured and methodical approach, ideal for stable environments, yet lacks flexibility in dynamic settings. Graph theory enhances the layout design process by optimizing spatial relationships between facilities through weighted planar graphs. The study highlights the strengths and limitations of each method, with a focus on their impact on material handling costs and overall layout efficiency. Among these, the combination of Genetic Algorithms (GA) and Stochastic Growth Algorithms (SGA) stands out, demonstrating significant reductions in material handling costs, up to 23.1%. The review concludes that while each methodology has its merits, the integration of GA and SGA offers the most robust solution for optimizing shipyard layouts, particularly in complex and large-scale environments. Future research should explore hybrid models that combine these methodologies, incorporating advanced computational techniques and real-time data analytics to create more dynamic and adaptable layout solutions, addressing the evolving needs of the shipbuilding industry.